Predictors Of Youth Conflict In Ebonyi State: The Perspective Of Christian Religion On The Conflict Managements - Clementina Njoku, Nkechi; Ebere Nwazonobi, Patricia; Margaret Ndidiamaka, Anugwo; Eni Eluu, Patrick; Adibe Nwafor, Kenneth; A Orji, Scholastica; C. Ngwakwe, Patricia; N. Afoke, Eunice; Ujebe, Nome; Francisca Nwakaego, Ede; Alor, Rosaline; OE. Nwoba, Martin; O. Aleke, Christian (International Journal of Educational Research & Social Sciences, 2024)
Conflict is an integral part of day- to-day life because when people live, associate and work together as a group, conflict is inevitable. The study determined predictors of youth’s conflict in ebonyi state and the perspective of Christian religion on the conflict managements. The study adopted a descriptive cross-sectional survey research design. The population of the study comprised all the youths in the affected communities of the State, while a total of three hundred (300) youths were selected using purposive sampling technique. Structured questionnaire were the instrument used for data collection. The analysis of data were done using mean and standard deviation. The findings reveals overall mean scores of ( = 3.1), which revealed that the items studied are high predictors of youth conflict in Ebonyi State. The result further shows the overall mean scores of ( = 3.2), which is above the criterion mean of 2.50, which indicated that conflict among the youth could be resolved/managed through Christian Religion education. The study concluded that the government at all levels and the concerned stakeholder of the communities should as a matter of fact imbibe and make the teaching and learning of Christian Religion studies compulsory in schools.